The Potential Value of Targeting Ferroptosis in Early Brain Injury After Acute CNS Disease - Chen, Junhui; Wang, Yuhai; Wu, Jiyun; Yang, Jiaji; Li, Mingchang; Chen, Qianxue (Frontiers in Molecular Neuroscience, 2020)
Acute central nervous system (CNS) disease is very common and with high mortality. Many basic studies have confirmed the molecular mechanism of early brain injury (EBI) after acute CNS disease. Neuron death and dysfunction are important reasons for the neurological dysfunction in patients with acute CNS disease. Ferroptosis is a nonapoptotic form of cell death, the classical characteristic of which is based on the iron-dependent accumulation of toxic lipid reactive oxygen species. Previous studies have indicated that this mechanism is critical in the cell death events observed in many diseases, including cancer, tumor resistance, Alzheimer’s disease, Parkinson’s disease, stroke, and intracerebral hemorrhage (ICH). Ferroptosis may also play a very important role in EBI after acute CNS disease. Unresolved issues include the relationship between ferroptosis and other forms of cell death after acute CNS disease, the specific molecular mechanisms of EBI, the strategies to activate or inhibit ferroptosis to achieve desirable attenuation of EBI, and the need to find new molecular markers of ferroptosis that can be used to detect and study this process in vivo after acute CNS disease.